How much vector control is needed to achieve malaria elimination? - Ulrich, Jill N. (2013)
Roll Back Malaria’s ambitious goals for global malaria reduction by 2015 represent a dilemma for National Malaria Control Programs (NMCPs) that are still far from malaria elimination. Current vector control efforts by NMCPs generally fall short of their potential, leaving many NMCPs wondering how much vector control it will take to achieve malaria elimination. We believe the answer is detailed in the relationships between the entomological inoculation rate (EIR) and four epidemiological measures of malaria in humans. To achieve adequate vector control NMCPs must evaluate EIRs to identify problematic foci of transmission and reduce annual EIRs to less than one infectious bite per person.